The effects of a proposed remedial program in algebra on the academic achievement of first year high school student of Benedictine Abbey School: school year 1988-1989 - Allanigue, Rachel E. (Animo Repository, 1989)
This study determines the effects of a proposed remedial program in high school Elementary Algebra on the academic achievement of first year students of Benedictine Abbey School for the school year 1988-1989. The subjects of the study were random samples of 52 students from the population of first year students of Benedictine Abbey School and first year students of Elizabeth Seton School. This study made use of two research designs namely, the research and development (R&D) design and the pre-test-post-test control group experimental design. This was primarily a research and development study because the proposed remedial program was developed after finding out the strengths and weaknesses of the students taking up first year remedial Mathematics. The proposed program was then implemented or field tested and subsequently evaluated by means of an experiment using the Pre-Test-Post-Test Group Design. Based on this design, the control and the experimental groups were given pre-tests, underwent different treatments and then given post-tests. The design is conceptualized with the use of the following illustration: 01 --------- X ---------0203 ---------NO X --------- 04 where: 01 and 03 were the pre-tests of both groups 02 and 04 were the post-tests of both groups and X was the treatment. The experimental group was given remedial instruction using programmed materials, computer-based lessons and audio-visual presentation. The control group underwent the usual traditional method of remedial instruction using lecture-discussion. Both groups (control and experimental) were given a pre-test on mathematics achievement. At the end of the program, both groups were given post-test on mathematics achievement. Their performances in the pre-and post- tests were compared and analyzed. Instruments used in the study were: Diagnostic Test in Mathematics I Pre-test and Post-test on the lesson content in mathematics Programmed materials Computer-based lessons and Audiovisual instructional materials. Based on the findings, the researcher concludes that the proposed remedial program using the following methods of instruction: Computer based ins truction, Audiovisual instruction and programmed instruction was generally effective in attaining better academic achievement on the part of the slow learners in Mathematics I.